2009
DOI: 10.1002/pbc.22053
|View full text |Cite
|
Sign up to set email alerts
|

Off‐label use of rFVIIa in children with excessive bleeding: A consecutive study of 153 off‐label uses in 139 children

Abstract: rFVIIa is an effective general hemostatic agent for management of excessive bleeding in children and that with the exception of neonates has excellent safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 5 publications
4
37
1
Order By: Relevance
“…The off label usage of rFVIIa in children has been reported in form of case reports and case series; and mostly have been a part of larger adult series. The authors could find a very few number of exclusive pediatric series [20,[24][25][26][27][28][29][30]. Out of these, series by Young et al (139 patients), Herbertson et al (265 patients) and Alten et al (135 patients); are larger than the present study [25,29,30].…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The off label usage of rFVIIa in children has been reported in form of case reports and case series; and mostly have been a part of larger adult series. The authors could find a very few number of exclusive pediatric series [20,[24][25][26][27][28][29][30]. Out of these, series by Young et al (139 patients), Herbertson et al (265 patients) and Alten et al (135 patients); are larger than the present study [25,29,30].…”
Section: Introductioncontrasting
confidence: 56%
“…(Table 6). The mean dose used in the present population group was 77 μgm/kg/dose, which is less than the other pediatric series [20,[24][25][26][27][28][29] .The authors tried to round off the dose to the nearest vial possible due to cost considerations. There is a definite reduction in the usage of blood components pre and post rFVIIa use in the present series matching the results of other studies [20,24,25,29,30].…”
Section: Response To Rfviia Mortality and Adverse Effectsmentioning
confidence: 97%
“…24 A recent study reporting on the safety 25 A clinical trial evaluating the off-label use of factor VIIa in the pediatric population revealed that thrombotic events occurred in 4.3% of children, of which the highest incidence developed in the neonatal population. 26 When assessing the risks and benefits of using rFVIIa, cost of therapy should be computed into the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study however, involved a heterogeneous group of patients with multiple background medical problems and various bleeding sites. Taking the subgroup of abdominal bleeding, their response is excellent in about 60% of their patients and ineffective in 13% 10 . Our results are fairly similar with 2 out of 3 patients where rFVIIa was effective.…”
Section: Case #3mentioning
confidence: 99%
“…In this study of 139 children from 1999-2005, the authors used a similar indication of starting rFVIIa (only when standard measures to control bleeding were undertaken) and similar methods to judge efficacy (3-point scale supported by measurement of transfusion of blood products 3 days prior and following the use of rFVIIa) 10 . This study however, involved a heterogeneous group of patients with multiple background medical problems and various bleeding sites.…”
Section: Case #3mentioning
confidence: 99%